An alkaline noble metal electrode

By using a composite catalytic layer composed of modified MXene and precious metals in the alkaline electrolytic water hydrogen production electrode, the structure and stability problems of the electrode under high current density are solved, and excellent electrocatalytic activity and long life are achieved.

CN118957672BActive Publication Date: 2025-05-02SHANGHAI JIPING NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411433946.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-05-02
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

In the prior art, it is difficult for the electrodes made of hydrogen by alkaline electrolysis to maintain long-term microstructure and mechanical stability under high current density, resulting in a decrease in electrocatalytic activity.

Method used

An alkaline noble metal electrode is used that includes a composite catalytic layer deposited on the surface of the nickel foam substrate. The composite catalytic layer consists of modified MXene and precious metals. The MXene is modified by solvent interpolation and ionic liquid, and is ultrasonic sprayed to the surface of the nickel foam, and then the precious metal layer is obtained by electrochemical deposition.

Benefits of technology

It achieves excellent electrocatalytic activity under high current density, extends the service life of the electrode, and improves the mechanical stability of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to an alkaline noble metal electrode, belonging to the technical field of electrocatalytic materials. The alkaline noble metal electrode prepared by the present invention comprises nickel foam and a composite catalytic layer deposited and fixed on the surface of the nickel foam substrate, wherein the composite catalytic layer comprises modified MXene and a noble metal, the MXene is modified by solvent intercalation and ionic liquid, ultrasonically sprayed on the surface of the nickel foam, and then the noble metal layer is obtained by electrochemical deposition, and the alkaline noble metal electrode prepared by the present invention has excellent electrocatalytic activity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrocatalytic materials and relates to an alkaline noble metal electrode. Background Art

[0002] Among various hydrogen production technologies, alkaline water electrolysis is the mainstream method for industrial green hydrogen production. Alkaline water electrolysis has the advantages of mature technology and long working life. However, water decomposition hydrogen production is still not economically comparable to steam methane reforming and coal gasification. The main bottleneck is high electricity cost and poor durability. Therefore, the electrode needs to maintain long-term microstructure and mechanical stability during water decomposition at ultra-high current density, so as to maintain excellent electrocatalytic activity.

[0003] At present, there are two types of water electrolysis catalysts: precious metal catalysts and non-precious metal catalysts. Although non-precious metal catalysts have low costs, their catalytic activity and stability are far lower than precious metal catalysts.

[0004] Therefore, it is necessary to develop a precious metal electrode that can be used in the alkaline water electrolysis process. Summary of the invention

[0005] The object of the present invention is to provide an alkaline noble metal electrode, and the prepared alkaline noble metal electrode has excellent electrocatalytic activity.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] An alkaline noble metal electrode, comprising nickel foam and a composite catalytic layer deposited and fixed on the surface of the nickel foam substrate, wherein the composite catalytic layer comprises modified MXene and a noble metal;

[0008] The preparation method of the alkaline noble metal electrode comprises the following steps:

[0009] S1. Nickel foam pretreatment:

[0010] The nickel foam was cleaned with ultrapure water and hydrochloric acid ultrasonically for 25-35 min, then ultrasonically treated with ultrapure water and ethanol for 20-30 min, and then vacuum dried at 50-80°C for 9-12 h.

[0011] S2. Preparation of MXene:

[0012] Ti3AlC2 was put into the etching solution at a solid-liquid ratio of 1: (10-20) g / mL, stirred at room temperature for 10-12 hours, centrifuged and washed with water after stirring to make the solution pH 6.6-7, and then ultrasonically treated with a power of 600-650 W for 1-2 hours. After ultrasonic stripping, it was centrifuged at a speed of 3000-3500 rpm for 0.5-1 hour, and the upper suspension was collected and dried to obtain MXene, wherein the etching solution was obtained by dissolving 1.5-3 mg of lithium fluoride in 20-25 mL of hydrochloric acid;

[0013] S3. Preparation of modified MXene:

[0014] The MXene with a solid-liquid ratio of 1: (20-25) g / mL was fully mixed with the intercalation agent, ultrasonically treated at room temperature for 6-11 hours, filtered and separated, and the obtained solid was washed with deionized water three times, and dried at 80-110 ° C for 8-12 hours to obtain the intercalated MXene;

[0015] The intercalated MXene is dispersed in deionized water to obtain a MXene suspension, tetrabutylammonium tetrafluoroborate is added to the MXene suspension, and the MXene suspension is treated at a temperature of 80-120° C. for 15-30 minutes by a microwave-assisted method. After the treatment, the modified MXene is filtered and dried at a temperature of 60-75° C. for 9-13 hours to obtain the modified MXene, wherein the mass ratio of the intercalated MXene, tetrabutylammonium tetrafluoroborate, and deionized water is (1-3): (0.5-1): (60-80);

[0016] S4. Re-disperse 20-25 parts of the dried modified MXene in 70-80 parts of deionized water to prepare a MXene dispersion, preheat the pretreated nickel foam on a 100°C hot baking plate for 5-8 minutes, spray the MXene dispersion onto the pretreated nickel foam by ultrasonic spraying, and wait for the surface to dry to obtain a modified MXene composite nickel foam;

[0017] S5. Place the modified MXene composite nickel foam in a soluble noble metal ion salt solution with a concentration of 2-4 mM, electrodeposit for 800-1100 seconds, rinse with deionized water and ethanol, and dry under vacuum conditions at 55-65° C. for 10-14 hours to obtain the alkaline noble metal electrode.

[0018] As a preferred technical solution of the present invention, in step S1, the hydrochloric acid has a concentration of 10-12 mol / L.

[0019] As a preferred technical solution of the present invention, in step S3, the intercalant is dimethyl sulfoxide and methyl isobutyl ketone in a volume ratio of 1: (1-2).

[0020] As a preferred technical solution of the present invention, in step S3, the microwave output power during microwave assistance is 700-800W.

[0021] As a preferred technical solution of the present invention, in step S4, the discharge rate of the ultrasonic spraying is 0.5-1 mL / min, and the speed is 50-100 mm / s.

[0022] As a preferred technical solution of the present invention, in step S5, the potential range of the electrodeposition is -1.5~0.5V, and the scanning rate is 5mV -1 , continue for 1 cycle.

[0023] As a preferred technical solution of the present invention, in step S5, the noble metal salt used in the soluble noble metal ion salt solution is one or more of palladium chloride, ammonium chloroiridate and sodium chlororhodate.

[0024] In the present invention, the nickel foam is pretreated to remove impurities on the surface of the nickel foam, thereby improving the activity of the nickel foam substrate to facilitate subsequent loading of the catalytic layer.

[0025] MAX material Ti3AlC2 is used as a precursor, and a mixed solution of LiF and HCl is used as an etchant to obtain MXene material. Dimethyl sulfoxide and methyl isobutyl ketone are mixed as solvent intercalation agents. The mixed use can enhance the solubility of MXene materials through a synergistic effect, help to more thoroughly intercalate the MXene materials, and at the same time improve the yield and quality of single-layer or few-layer MXene; after dimethyl sulfoxide and methyl isobutyl ketone are mixed, due to their excellent solubility, they can more effectively penetrate the interlayers of MXene and promote the intercalation process. During the intercalation process, dimethyl sulfoxide is mainly responsible for intercalation and increasing the interlayer spacing, while methyl isobutyl ketone is adsorbed on the surface of MXene through the interaction of van der Waals forces to form one or more solvation layers, helping dimethyl sulfoxide to overcome the interlayer resistance and enter the interlayers of MXene for intercalation.

[0026] The intercalated MXene is treated with the ionic liquid tetrabutylammonium tetrafluoroborate. On the one hand, the ionic liquid can improve the conductivity of the MXene material and accelerate the ion migration rate, thereby improving the charge and discharge rate performance of the battery. In addition, the addition of tetrabutylammonium tetrafluoroborate can stabilize the electrochemical properties of the MXene material, reduce the performance decay in the electrochemical process, and improve the long-term cycle stability. At the same time, tetrabutylammonium tetrafluoroborate is hydrophobic, which can adjust the surface properties of the MXene material and improve the hydrophobicity of the electrode. In the electrocatalytic process, water molecules are not easy to form a water film on the electrode surface, so that electrons and ions can be transferred more smoothly on the electrode surface, accelerating the electrochemical reaction, thereby improving the electrocatalytic activity; at the same time, by improving the hydrophobicity of the electrode, the decay rate of the electrode during long-term use can be slowed down, extending the service life of the electrode. The ionic liquid can enter the interlayer of the MXene material through intercalation, thereby further optimizing the interlayer structure.

[0027] The modified MXene, in which the intercalation treatment helps to peel off the multi-layer MXene into a single-layer or few-layer structure, has a higher specific surface area, thereby increasing the transmission path of carriers (such as electrons or holes), which is beneficial to the improvement of electrode conductivity; and by regulating the interlayer spacing of MXene through modification treatment, optimizing the interlayer interaction and charge transfer channel, it can reduce interlayer scattering, improve the mobility of carriers, and then increase conductivity, which can more effectively transfer electrons, thereby reducing energy loss during electrolysis, and helping to improve the rate and efficiency of water electrolysis reaction.

[0028] At the same time, in alkaline environments, MXene materials exhibit good chemical stability, which helps to extend the service life of the electrode.

[0029] After forming a layer of modified MXene on the surface of nickel foam by ultrasonic spraying, precious metals are deposited on the surface by electrodeposition. When the precious metals are deposited on the surface of the modified MXene material, the high specific surface area and rich functional groups of the modified MXene material provide more attachment points and reactive sites for the precious metals, which can further improve the catalytic activity of the electrode. At the same time, the deposition of precious metals can form a conductive network on the surface or enhance the electron transmission channel to further improve the conductivity of the electrode. The good contact between the precious metal and the modified MXene can reduce the interface resistance, promote the rapid transmission of electrons between the electrode and the electrolyte, and improve the response speed and efficiency of the electrode. The MXene material itself has good mechanical properties and chemical stability. When combined with precious metals, it can form a more stable electrode structure, reduce structural changes during charging and discharging or electrocatalysis, and improve the mechanical stability of the electrode, thereby helping to improve the overall electrocatalytic activity.

[0030] Beneficial effects of the present invention:

[0031] The alkaline noble metal electrode prepared by the present invention comprises nickel foam and a composite catalytic layer deposited and fixed on the surface of the nickel foam substrate, wherein the composite catalytic layer comprises modified MXene and a noble metal, the MXene is modified by solvent intercalation and ionic liquid, ultrasonically sprayed onto the surface of the nickel foam, and then the noble metal layer is obtained by electrochemical deposition. The alkaline noble metal electrode prepared by the present invention has excellent electrocatalytic activity. DETAILED DESCRIPTION

[0032] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0033] In the following examples and comparative examples:

[0034] Nickel foam: purchased from Kunshan Daipinghu Electronic Technology Co., Ltd.

[0035] Ti3AlC2: purchased from Beijing Huawei Ruike Chemical Technology Co., Ltd.;

[0036] Dimethyl sulfoxide: purchased from Shanghai Haohong Biopharmaceutical Technology Co., Ltd., product number: 1083196;

[0037] Methyl isobutyl ketone: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: M108740;

[0038] Tetrabutylammonium tetrafluoroborate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: T824188;

[0039] Palladium chloride: purchased from Zhengzhou Aikemu Chemical Co., Ltd.

[0040] Ammonium chloroiridate: purchased from Jiangsu Boquan Biotechnology Co., Ltd.;

[0041] Sodium chlororhodium salt: purchased from Shanghai Myrel Biochemical Technology Co., Ltd.

[0042] Example 1

[0043] S1. Nickel foam pretreatment:

[0044] The nickel foam was ultrasonically cleaned with ultrapure water and 10 mol / L hydrochloric acid for 25 min, then ultrasonically treated with ultrapure water and ethanol for 20 min, and then vacuum dried at 50 °C for 9 h.

[0045] S2. Preparation of MXene:

[0046] Ti3AlC2 was put into the etching solution at a solid-liquid ratio of 1:10 g / mL, stirred at room temperature for 10 h, centrifuged and washed with water after stirring to make the solution pH 6.6, and then ultrasonically treated for 1 h with a power of 600 W. After ultrasonic stripping, it was centrifuged at a speed of 3000 rpm for 0.5 h, and the upper suspension was collected and dried to obtain MXene, wherein the etching solution was obtained by dissolving 1.5 mg of lithium fluoride in 20 mL of hydrochloric acid;

[0047] S3. Preparation of modified MXene:

[0048] The MXene with a solid-liquid ratio of 1:20 g / mL was fully mixed with an intercalation agent, subjected to ultrasonic treatment at room temperature for 6 h, filtered and separated, and the obtained solid was washed with deionized water 3 times, and dried at 80 °C for 8 h to obtain the intercalated MXene. The intercalation agent was dimethyl sulfoxide and methyl isobutyl ketone in a volume ratio of 1:1.

[0049] The intercalated MXene is dispersed in deionized water to obtain a MXene suspension, tetrabutylammonium tetrafluoroborate is added to the MXene suspension, and a microwave-assisted method with an output power of 700 W is used to treat the MXene at a temperature of 80° C. for 15 minutes. After the treatment, the modified MXene is obtained by filtering and drying at a temperature of 60° C. for 9 hours, wherein the mass ratio of the intercalated MXene, tetrabutylammonium tetrafluoroborate, and deionized water is 1:0.5:60;

[0050] S4. Re-disperse 20 parts of the dried modified MXene into 70 parts of deionized water to prepare a MXene dispersion, place the pretreated nickel foam on a hot baking plate at 100°C for 5 minutes, spray the MXene dispersion onto the pretreated nickel foam by ultrasonic spraying, wait for the surface to dry, and obtain a modified MXene composite nickel foam. The discharge rate of the ultrasonic spraying is 0.5 mL / min and the speed is 50 mm / s.

[0051] S5. The modified MXene composite nickel foam was placed in a 2 mM palladium chloride solution, and electroplated for 800 s. The solution was then rinsed with deionized water and ethanol, and dried at 55-65 °C under vacuum for 10 h to obtain the alkaline noble metal electrode. The potential range during electroplating was -1.5 V, and the scanning rate was 5 mV. -1 , continue for 1 cycle.

[0052] Example 2

[0053] S1. Nickel foam pretreatment:

[0054] The nickel foam was ultrasonically cleaned with ultrapure water and 11 mol / L hydrochloric acid for 30 min, then ultrasonically treated with ultrapure water and ethanol for 25 min, and then vacuum dried at 70 °C for 10 h.

[0055] S2. Preparation of MXene:

[0056] Ti3AlC2 was put into the etching solution at a solid-liquid ratio of 1:15 g / mL, stirred at room temperature for 11 hours, centrifuged and washed with water to make the solution pH 6.8, and then ultrasonically treated with a power of 630 W for 1.5 hours. After ultrasonic stripping, it was centrifuged at a speed of 3300 rpm for 0.8 hours, and the upper suspension was collected and dried to obtain MXene, wherein the etching solution was obtained by dissolving 2 mg of lithium fluoride in 22 mL of hydrochloric acid;

[0057] S3. Preparation of modified MXene:

[0058] The MXene with a solid-liquid ratio of 1:23 g / mL was fully mixed with an intercalation agent, ultrasonically treated at room temperature for 8 h, filtered and separated, and the obtained solid was washed with deionized water 3 times and dried at 90 °C for 10 h to obtain the intercalated MXene. The intercalation agent was dimethyl sulfoxide and methyl isobutyl ketone with a volume ratio of 1:1.5;

[0059] The intercalated MXene is dispersed in deionized water to obtain a MXene suspension, tetrabutylammonium tetrafluoroborate is added to the MXene suspension, and a microwave-assisted method with an output power of 750 W is used to treat the MXene at a temperature of 100° C. for 20 minutes. After the treatment, the modified MXene is obtained by filtering and drying at a temperature of 68° C. for 11 hours, wherein the mass ratio of the intercalated MXene, tetrabutylammonium tetrafluoroborate, and deionized water is 2:0.8:70;

[0060] S4. Re-disperse 22 parts of the dried modified MXene in 75 parts of deionized water to prepare a MXene dispersion, place the pretreated nickel foam on a hot baking plate at 100°C for 7 minutes, spray the MXene dispersion onto the pretreated nickel foam by ultrasonic spraying, wait for the surface to dry, and obtain a modified MXene composite nickel foam. The discharge rate of the ultrasonic spraying is 0.8 mL / min and the speed is 80 mm / s.

[0061] S5. The modified MXene composite nickel foam was placed in a 3 mM ammonium chloroiridate solution, and electrodeposited for 900 s. The electrodeposited material was then rinsed with deionized water and ethanol, and dried at 60 °C under vacuum for 12 h to obtain the alkaline noble metal electrode. The potential range during electrodeposition was -0.5 V, and the scan rate was 5 mV. -1 , continue for 1 cycle.

[0062] Example 3

[0063] S1. Nickel foam pretreatment:

[0064] The nickel foam was ultrasonically cleaned with ultrapure water and 12 mol / L hydrochloric acid for 35 min, then ultrasonically treated with ultrapure water and ethanol for 30 min, and then vacuum dried at 80 °C for 12 h.

[0065] S2. Preparation of MXene:

[0066] Ti3AlC2 was put into the etching solution at a solid-liquid ratio of 1:20 g / mL, stirred at room temperature for 12 hours, centrifuged and washed with water after stirring to make the solution pH 7, and then ultrasonically treated for 2 hours with a power of 650 W. After ultrasonic stripping, it was centrifuged at a speed of 3500 rpm for 1 hour, and the upper suspension was collected and dried to obtain MXene, wherein the etching solution was obtained by dissolving 3 mg of lithium fluoride in 25 mL of hydrochloric acid;

[0067] S3. Preparation of modified MXene:

[0068] The MXene with a solid-liquid ratio of 1:25 g / mL was fully mixed with an intercalation agent, ultrasonically treated at room temperature for 11 h, filtered and separated, and the obtained solid was washed with deionized water 3 times and dried at 110 °C for 12 h to obtain the intercalated MXene. The intercalation agent was dimethyl sulfoxide and methyl isobutyl ketone with a volume ratio of 1:2.

[0069] The intercalated MXene is dispersed in deionized water to obtain a MXene suspension, tetrabutylammonium tetrafluoroborate is added to the MXene suspension, and a microwave-assisted method with an output power of 800 W is used to treat the MXene at a temperature of 120° C. for 30 minutes. After the treatment, the modified MXene is obtained by filtering and drying at a temperature of 75° C. for 13 hours, wherein the mass ratio of the intercalated MXene, tetrabutylammonium tetrafluoroborate, and deionized water is 3:1:80;

[0070] S4. Re-disperse 25 parts of the dried modified MXene in 80 parts of deionized water to prepare a MXene dispersion, preheat the pretreated nickel foam on a hot baking plate at 100°C for 8 minutes, spray the MXene dispersion onto the pretreated nickel foam by ultrasonic spraying, wait for the surface to dry, and obtain a modified MXene composite nickel foam. The discharge rate of the ultrasonic spraying is 1 mL / min and the speed is 100 mm / s.

[0071] S5. The modified MXene composite nickel foam was placed in a 4 mM sodium chlororhodate solution, and electrodeposited for 1100 s. The electrodeposited material was then rinsed with deionized water and ethanol, and dried at 65 °C under vacuum for 14 h to obtain the alkaline noble metal electrode. The potential range during electrodeposition was 0.5 V, and the scanning rate was 5 mV. -1 , continue for 1 cycle.

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that the intercalation agent in Comparative Example 1 is dimethyl sulfoxide, and the other operations are the same.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that the modified MXene in Comparative Example 2 is not treated with tetrabutylammonium tetrafluoroborate during the preparation process, and the other operations are the same.

[0076] Comparative Example 3

[0077] The difference between Comparative Example 3 and Example 1 is that the MXene in Comparative Example 3 is not modified, and the other operations are the same.

[0078] Performance Testing:

[0079] The alkaline noble metal electrodes prepared in Examples 1-3 and Comparative Examples 1-3 were used as working electrodes, saturated calomel electrode was used as reference electrode, and carbon rod was used as counter electrode. The electrochemical performance was tested in 1M KOH solution using a Chenhua 760D electrochemical workstation.

[0080] 1. Test at a current density of 500mA / cm 2 The overpotential for hydrogen evolution at:

[0081] 2. Test the current density at 1.6V. The test results are as follows:

[0082]

[0083] According to the above data, at 500mA cm -2 The hydrogen evolution overpotentials of the embodiments were 259 mV, 245 mV, and 240 mV respectively at the current density, which all met the requirements of the alkaline electrolytic cell at 500 mA cm -2 The overpotential does not exceed the application requirement of 300mV at the current density, indicating that the catalyst has good catalytic activity. And the current density is higher at the same voltage, indicating that the electrode prepared in the embodiment has higher electrolysis efficiency, so the catalytic activity of the embodiment is higher and the electrochemical performance is more excellent.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. An alkaline noble metal electrode, characterized in that The alkaline noble metal electrode comprises nickel foam and a composite catalytic layer deposited and fixed on the surface of the nickel foam substrate, wherein the composite catalytic layer comprises modified MXene and a noble metal; The preparation method of the alkaline noble metal electrode comprises the following steps: S1. Nickel foam pretreatment: The nickel foam was cleaned with ultrapure water and hydrochloric acid ultrasonically for 25-35 min, then ultrasonically treated with ultrapure water and ethanol for 20-30 min, and then vacuum dried at 50-80°C for 9-12 h. S2. Preparation of MXene: Ti3AlC2 was put into the etching solution at a solid-liquid ratio of 1: (10-20) g / mL, stirred at room temperature for 10-12 hours, centrifuged and washed with water after stirring to make the solution pH 6.6-7, and then ultrasonically treated with a power of 600-650 W for 1-2 hours. After ultrasonic stripping, it was centrifuged at a speed of 3000-3500 rpm for 0.5-1 hour, and the upper suspension was collected and dried to obtain MXene, wherein the etching solution was obtained by dissolving 1.5-3 mg of lithium fluoride in 20-25 mL of hydrochloric acid; S3. Preparation of modified MXene: The MXene with a solid-liquid ratio of 1: (20-25) g / mL and the intercalation agent are fully mixed, ultrasonically treated at room temperature for 6-11 hours, filtered and separated, and the obtained solid is washed with deionized water for 3 times, and dried at 80-110°C for 8-12 hours to obtain the intercalated MXene, wherein the intercalation agent is dimethyl sulfoxide and methyl isobutyl ketone with a volume ratio of 1: (1-2); The intercalated MXene is dispersed in deionized water to obtain a MXene suspension, tetrabutylammonium tetrafluoroborate is added to the MXene suspension, and the MXene suspension is treated at a temperature of 80-120° C. for 15-30 minutes by a microwave-assisted method. After the treatment, the modified MXene is filtered and dried at a temperature of 60-75° C. for 9-13 hours to obtain the modified MXene, wherein the mass ratio of the intercalated MXene, tetrabutylammonium tetrafluoroborate, and deionized water is (1-3): (0.5-1): (60-80); S4. Re-disperse 20-25 parts of the dried modified MXene in 70-80 parts of deionized water to prepare a MXene dispersion, preheat the pretreated nickel foam on a 100°C hot baking plate for 5-8 minutes, spray the MXene dispersion onto the pretreated nickel foam by ultrasonic spraying, and wait for the surface to dry to obtain a modified MXene composite nickel foam; S5. Place the modified MXene composite nickel foam in a soluble precious metal ion salt solution with a concentration of 2-4 mM, electrodeposit for 800-1100 seconds, rinse with deionized water and ethanol, and dry under vacuum conditions at 55-65°C for 10-14 hours to obtain the alkaline precious metal electrode, wherein the precious metal salt used in the soluble precious metal ion salt solution is one or more of palladium chloride, ammonium chloroiridate and sodium chlororhodate.

2. The alkaline noble metal electrode according to claim 1, characterized in that In step S1, the hydrochloric acid has a concentration of 10-12 mol / L.

3. The alkaline noble metal electrode according to claim 1, characterized in that In step S3, the microwave output power is 700-800W during microwave assistance.

4. The alkaline noble metal electrode according to claim 1, characterized in that In step S4, the discharge rate of the ultrasonic spraying is 0.5-1 mL / min, and the speed is 50-100 mm / s.

5. The alkaline noble metal electrode according to claim 1, characterized in that In step S5, the potential range of the electrodeposition is -1.5~0.5V, and the scanning rate is 5mV -1 , continue for 1 cycle.